MEGANTHIAS KINGYO (KON, YOSHINO AND SAKURAI, 2000) (PERCIFORMES: SERRANIDAE) FROM BITUNG, NORTH SULAWESI, INDONESIA: FIRST RECORD FROM THE SOUTHWESTERN PACIFIC OCEAN - Peristiwady, Teguh; Koagouw, Wulan; Du, Jianguo; Makatipu, Petrus Christianus (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
Eight specimens of Meganthias kingyo were collected from Bitung, North Sulawesi, Indonesia between 2008 - 2010. The specimens were caught from about 70-150 m off Lembeh Island. M. kingyo differs from M. natalensis by having the following characteristics: pores lateral line scales (43 vs. 49); pectoral rays (16 vs. ii.14); body depth (47.1 vs. 51.9); head length (31.0 vs. 38.2), body depth (47.1 vs. 52.9), caudal peduncle depth (12.1 vs. 14.2), pectoral fin length (28.0 vs. 34.3), pelvic fin length (33.6 vs. 31.1), anal fin base length (19.4 vs. 22.2), caudal fin length (66.9 vs. 35.3) and longest dorsal fin ray (48.5 vs. 27.4). Previously, this species has been reported from Houzan-sone, off Miyako and Yaeyama Islands in Okinawa, Japan; and herein is recorded from off Lembeh Island, North Sulawesi, Indonesia.